Tradisi Teng-Tengan, Ketuwinan dan Weh-Wehan di Kaliwungu Kendal Jawa Tengah (Kajian Living Hadis Pendekatan Antropologi Interpretatif Simbolik) - Ghufron Hamzah; Iman Fadhilah (UPT Pusat Studi Aswaja UNISNU Jepara, 2022)
AbstractTradition is a continuous activity carried out by a social community that has been running for a very long period of time. Including the teng-tengan, ketuwinan and weh-wehan traditions in Kaliwungu. This research was conducted to find out the history and implementation of this tradition. First, how the origins and traditions are carried out, Second, the relevance of living hadith studies with a symbolic interpretative anthropological approach in looking at the teng-tengan, ketuwinan and weh-wehan traditionsin Kaliwungu. Methods of data collection are carried out through observation, interviews, as well as documentation including references relevant to the study. While the data analysis used is descriptive qualitative with a symbolic interpretative anthropological approach. According to Geertz, the joyful expression symbolized in the tengengan tradition is because religion influences mood and motivation / creates strong feelings and motivations for its adherents and in the end, these feelings and motivations will be seen as a unique reality, a tradition passed down from generation to generation. Symbols in the form of physical (tengan / lanterns) and symbols in the form of actions (ketuwinan and weh-wehan) of this tradition are loaded with the actualization ofinformative and performative values from normative teachings about the virtues of the Prophet Muhammad. This research has theoretical implications for the domain of living hadith from an anthropological perspective. At least the Javanese people still accommodate cultural values in religious ritual practices.Keywords: Teng-tengan Tradition, Ketuwinan and Weh-wehan, Living Hadith, Symbolic Interpretive Anthropology.AbstrakTradisi merupakan kegiatan terus menerus yang dilakukan sebuah komunitas sosial yang sudah berjalan dalam kurun waktu yang sangat panjang. Termasuk tradisi teng-tengan, ketuwinan dan weh-wehan yang ada di Kaliwungu. Penelitian ini dilakukan untuk mengetahui sejarah dan pelaksanaan tradisi tersebut. Pertama, bagaimana asal mula dan tradisi tersebut dilakukan, Kedua, relevansi kajian living hadis dengan pendekatan antropologi interpretatif simbolik dalam melihat tradisi teng-tengan, ketuwinan dan weh-wehan di Kaliwungu. Metode pengumpulan data dilakukan melalui observasi, wawancara, serta dokumentasi termasuk referensi yang relevan dengan kajian. Sedangkan analisis data yang digunakan adalah deskriptif kualitatif dengan pendekatan antropologi interpretatif simbolik. Ekspresi gembira yang tersimbolkan dalam tradisi teng-tengan itu menurut Geertz karena agama mempengaruhi mood and motivation / menciptakan perasaan dan motivasi yang kuat bagi pemeluknya dan pada akhirnya perasaan dan motivasi ini akan terlihat sebagai suatu realitas yang unik, tradisi yang turun temurun. Simbol berupa fisik (teng-tengan /lampion) maupun simbol berupa tindakan (ketuwinan dan weh-wehan) tradisi ini sarat dengan aktualisasi nilai-nilai informatif dan performatif dari ajaran normatif tentang keutamaan Nabi Muhammad saw.Kata Kunci: Tradisi Teng-tengan, Ketuwinan dan Weh-wehan, Living Hadis, Antroplogi Interpretatif Simbolik.